2010
DOI: 10.1074/jbc.m110.162073
|View full text |Cite
|
Sign up to set email alerts
|

An NAADP-gated Two-pore Channel Targeted to the Plasma Membrane Uncouples Triggering from Amplifying Ca2+ Signals

Abstract: Nicotinic acid adenine dinucleotide phosphate (NAADP) is a ubiquitous messenger proposed to stimulate Ca2+ release from acidic organelles via two-pore channels (TPCs). It has been difficult to resolve this trigger event from its amplification via endoplasmic reticulum Ca2+ stores, fuelling speculation that archetypal intracellular Ca2+ channels are the primary targets of NAADP. Here, we redirect TPC2 from lysosomes to the plasma membrane and show that NAADP evokes Ca2+ influx independent of ryanodine receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
257
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(279 citation statements)
references
References 37 publications
19
257
2
1
Order By: Relevance
“…6), provide firm evidence that TRPML1 is not a target for NAADP and support TPCs as NAADP-activated channels. Indeed, our conclusions are consistent with three recent studies reporting channel activity for TPC2 from isolated lysosomes, immunopurified TPC2 fused into lipid bilayers, or in cells expressing plasma membrane targeted TPC2 (42,49,50). Importantly, in two of these studies, currents were eliminated or modified by mutations in the putative channel pore (42,50).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…6), provide firm evidence that TRPML1 is not a target for NAADP and support TPCs as NAADP-activated channels. Indeed, our conclusions are consistent with three recent studies reporting channel activity for TPC2 from isolated lysosomes, immunopurified TPC2 fused into lipid bilayers, or in cells expressing plasma membrane targeted TPC2 (42,49,50). Importantly, in two of these studies, currents were eliminated or modified by mutations in the putative channel pore (42,50).…”
Section: Discussionsupporting
confidence: 82%
“…However, it is possible that the TPCs are not targeted to the plasma membrane even when overexpressed, thereby explaining the lack of affect on TRPML activity. The N terminus of TPC2 contains a lysosomal targeting di-leucine motif (42). In a recent study, we showed that N-terminally truncated TPC2 (TPC2delN) is targeted to the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutant of TPC2 lacking a di-leucine motif in its N-terminal has recently been shown to be localized to the PM instead of the lysosomal membrane, suggesting that this motif is required for its localization to acidic organelles. 28 Plant TPC family members including OsTPC1 possess a similar motif in their N-terminal tail, which is consistent with the localization to the VM. The PM localization of OsTPC1 in cultured rice cells 15,20 suggests some differences in sorting machinery of the TPC family membrane proteins among plant species.…”
Section: Intracellular Localization and Physiological Function Of A Rsupporting
confidence: 78%
“…54,60,61 N-Linked glycosylation is the process whereby carbohydrate residues are added to asparagine residues of proteins, specifically a subset residing in the Asn-X-Ser/Thr motif (where X is any residue except proline), that can affect many key biological processes including cell adhesion, molecular trafficking and clearance, receptor activation, signal transduction, and endocytosis. 62 Both TPC1 and TPC2 are N-glycosylated conforming to the consensus Asn-X-Ser/Thr at residues 599, 611, and TPC1 has an additional glycosylation site at residue 616.…”
Section: Structurementioning
confidence: 99%